Post-PE impairment: Living with uncertainty following pediatric pulmonary embolism. (March 2020) - Schaefer, Beverly
Abstract: Post-Pulmonary Embolism impairment (PPEI), also called Post-PE syndrome is being increasingly recognized as a long-term sequelae of pulmonary embolism (PE) in adults, but data regarding its prevalence in pediatrics is unknown. PPEI likely represents a spectrum of severity, with the most severe manifestation being chronic thromboembolic pulmonary hypertension (CTEPH) affecting a small proportion of individuals, and with many individuals with less severe PPEI suffering from reduced quality of life and functional limitations. The pathophysiology is poorly understood but involves residual pulmonary artery thrombi leading to right ventricular damage and abnormal gas exchange. The prevalence, risk factors and a consensus definition in the pediatric and adolescent populations is unknown, as are optimum treatment strategies. In addition to physical sequelae, psychological consequences of PE are significant and also under recognized. Highlights: Rates of pulmonary embolism are rising in pediatrics. Long term physical and psychological sequelae of pulmonary embolism are underrecognized. Post-PE Impairment encompasses a spectrum of clinical severity. Chronic thromboembolic pulmonary hypertension is a severe complication after PE. Future research is needed regarding long-term outcomes in pediatric PE.